Predictors for Asthma Formation in School-Age Children in Ternopil Region - E.I. Burbela (Zaslavsky O.Yu., 2016)
Background. Algorithm of screening diagnostics for bronchial asthma (BA) to identify asthma susceptibility forces doctors of a first contact to a differentiated approach to the compilation of forecasting, individual treatment and rehabilitation programs. The aim of the study was to investigate the risk of asthma in school-age children. Materials and methods. 121 children with asthma treated at Ternopil region children hospital during 2012-2016 were studied. The control group consisted of 226 adolescents, of which 76.55 % (n  =  173) apparently healthy children at the time of examination were secondary school urban students and 2.45 % (n  =  53) - rural students. The average age of patients investigated was 12.98 ± 2.80 years old and 12.36 ± 2.80 years old in the control group. The study was conducted with regard to the basic principles of the Helsinki Declaration on Biomedical Research and provisions GCH ICH, compliance with ethical principles and guidelines involving people as subjects set out in Belmont Report. Results and discussion. Based on a simple ranking value %AR factors playinbg a major role in causing asthma were considered as a level above 50 %. These predictors were: maintenance of diathesis manifestations after the first year of life, оbstructive bronchitis, passive smoking, burdened heredity for atopy, atopic dermatitis, high personal anxiety, high and medium situational anxiety, general school anxiety, social stress, frustration at needs to succeed, fear expression and fear of knowledge test, fear not to match to the expectations of others, low resistance to physiological stress, the presence of autonomic dysfunction, high (70 cu) Robinson index. Seven contributing factors in the formation of BA level above 25 % were determined: atopic manifestations on the skin up to a year, the presence of phlegmatic temperament, and eutonia and vagotony according to the Kerdem index, Robinson index above average (71-75 cu). Conclusions. Thus, the study of relative and attributive risk for asthma in students allow determine a group of the managed predictors of asthma in school-age children. Calculation of individual risk in a cohort of pupils in relatively healthy within in-depth examination with the proposed complex of psychosomatic screening examination allows determine a group with an increased risk of asthma and perform spirometric examination to confirm the diagnosis.